Introducing Listening to Adult Learners- ’The Fun Way’ - Tofail, Faria (EAST WEST JOURNAL OF HUMANITIES, 2011)
Using songs to practice listening skills is not a new concept. However, in the context of English Language Teaching (ELT) in Bangladesh where listing remains the least practiced and most neglected of the four basic shills up till the higher secondary level of education , the very idea of listening to a recorded speech in a foreign accent far removed from whatever English they have been exposed to, appears to be quite intimidating to most learners, especially young adults in Bangladesh, are pretty much into English music, it can be used as both a familiar and interesting resource requiring minimum of logistics support, and enhancing student participation in promoting and developing their listening skills. this paper will also discuss issues relating to maximizing listening inputs in language classrooms by using songs, the kinds of songs to be chosen, and ways to use them effectively in such classes. Keeping in view the practical constraints of using listening activities in the language classrooms in Bangladesh, the paper sets out to provide useful suggestions on using songs embracing a whole spectrum of activities designed to promote acquisition, entertainments as well as production of the target language for adult learners.